Aerospace Structures - Johnson, Eric Raymond (Open textbook library., 2022)
Aerospace Structures by Eric Raymond Johnson is a 600+ page text and reference book for junior, senior, and graduate-level aerospace engineering students. The text begins with a discussion of the aerodynamic and inertia loads acting on aircraft in symmetric flight and presents a linear theory for the status and dynamic response of thin-walled straight bars with closed and open cross-sections. Isotropic and fiber-reinforced polymer (FRP) composite materials including temperature effects are modeled with Hooke’s law. Methods of analyses are by differential equations, Castigliano’s theorems, the direct stiffness method, the finite element method, and Lagrange’s equations. There are numerous examples for the response axial bars, beams, coplanar trusses, coplanar frames, and coplanar curved bars. Failure initiation by the von Mises yield criterion, buckling, wing divergence, fracture, and by Puck’s criterion for FRP composites are presented in the examples. Professors, if you are considering or reviewing this book for adoption in your course, please let us know here. Problem sets: http://hdl.handle.net/10919/104169 ePub and LaTeX source files: Expected late spring 2022